Pregnancy outcomes in patients with undifferentiated connective tissue disease: An observational cohort prospective study - E. N. Grudnitskaya; L. M. Nebyshynets (Кубанский научный медицинский вестник, 2024)
Background. Undifferentiated connective tissue disease is the subject of research in a large number of medical specialties, as it leads to an aggravated course of various diseases. In the presence of this pathology during pregnancy, the incidence of such complications as preeclampsia, gestational diabetes, and placental abruption increases. Failure to carry a pregnancy to term can be associated with various causes, including the activity of myocytes, while the pathology in question involves the connective tissue of the uterus. In this connection, it seems necessary to study the impact of undifferentiated connective tissue disease on pregnancy outcomes in order to administer timely treatment.Objectives. To assess how undifferentiated connective tissue disease affects the risk of failure to carry a pregnancy to term.Methods. An observational cohort prospective study was conducted among pregnant women who were under antenatal care in 2021–2022. The study was performed at the premises of the Clinical Maternity Hospital of Minsk Region (Republic of Belarus). The patients were divided into two groups: an exposed group comprising 59 patients with diagnosed undifferentiated connective tissue disease and a nonexposed group comprising 59 patients without this pathology. Both groups were divided into subgroups according to the obstetric outcome. The exposed group included a subgroup of 17 undifferentiated connective tissue disease patients who had failed to carry pregnancy to term (miscarriage and preterm labor) and a subgroup of 42 undifferentiated connective tissue disease patients with delivery at term. The nonexposed group included a subgroup of five women without undifferentiated connective tissue disease who had failed to carry pregnancy to term (miscarriage and preterm labor) and a subgroup of 54 women without undifferentiated connective tissue disease and with delivery at term. According to ICD-10, abortive outcomes occurred before 21 weeks and six days gestation; labor that occurred at 22–36 weeks and six days gestation was considered preterm, whereas in the case of delivery at term, the baby was born at 37–41 weeks and six days gestation. The obstetric, gynecological, and somatic history, as well as pregnancy outcomes, were analyzed. Statistical processing of data was performed using the following software: Statistica 12.0 (StatSoft, USA), Microsoft Excel 2016, Epi InfoTM 7.2.6.0 (USA), and MedCalc 15.8 (MedCalc Software, Belgium). In hypothesis testing, differences were considered statistically significant at p < 0.05.Results. In the group of undifferentiated connective tissue disease patients, metrorrhagia was statistically significantly more common than in the patients without undifferentiated connective tissue disease: 18 out of 59 (30.5 %) and six out of 59 (10.2 %), respectively, p = 0.012. The obstetric history revealed no statistically significant intergroup differences, p > 0.05. In the undifferentiated connective tissue disease patients, the following diseases were statistically significantly more common: myopia, spinal scoliosis, lower limb varicose veins, chronic tonsillitis, mitral valve prolapse, and iron deficiency anemia (p < 0.05). The incidence of new cases of failure to carry a pregnancy to term in the cohort during the observation period amounted to 18.6 % for the patients in both groups. The pregnancy ended prematurely in 17 out of the 59 undifferentiated connective tissue disease patients (28.8 %) and in five out of the 59 patients without undifferentiated connective tissue disease (8.5 %), relative risk of 3.4 (95 % CI:1.3–8.6), p = 0.005.Conclusion. Undifferentiated connective tissue disease increases the risk of failure to carry a pregnancy to term by 3.4 times. Timely diagnosis and treatment of undifferentiated connective tissue disease at the stage of preconception preparation can reduce the incidence of failure to carry a pregnancy to term.